Lessons of Government Failure: Public Goods Provision and Quality of Public Investment - Arvind Virmani (Planning Commission Government of India, 2006)
This paper, Lessons of Government Failure: Public Goods Provision and Quality of Public Investment by Arvind Virmani (2006), critically examines the effectiveness of government intervention in India by comparing the period of Indian Socialism (1950–1980) with the subsequent era of market-oriented reforms. The study highlights the limitations of state-led development, demonstrating that public investment is neither a necessary nor sufficient condition for sustained economic growth or poverty reduction. Empirical analysis reveals a weak correlation between government investment and GDP growth, emphasizing the superior role of private consumption and private investment in driving productivity and economic expansion. The paper attributes policy failures to inefficient allocation of public resources, weak governance, and bureaucratic constraints. It advocates a strategic reorientation of government functions towards the provision of core public goods, strengthening regulatory institutions, and fostering public–private partnerships. Overall, the study calls for improved governance and greater private sector participation to enhance economic efficiency, social welfare, and long-term growth.
Planning Commission Government of India February, 2006
Keywords: Government Failure; Public Goods Provision; Public Investment Quality; Indian Socialism; Market Reforms; Private Consumption; Economic Growth; Poverty Reduction; Governance Reforms; Public-Private Partnerships; Infrastructure Investment; Regulatory Frameworks